Dust reverberation mapping of type 2 AGN NGC 2110 realized with X-ray and 3–5 μm IR monitoring. Issue 3 (20th May 2020) - Noda, Hirofumi; Kawamuro, Taiki; Kokubo, Mitsuru; Minezaki, Takeo
ABSTRACT: The dust reverberation mapping is one of powerful methods to investigate the structure of the dusty tori in active galactic nuclei (AGNs), and it has been performed on more than a hundred type 1 AGNs. However, no clear results have been reported on type 2 AGNs because their strong optical/UV extinction completely hides their accretion disc emission. Here, we focus on an X-ray-bright type 2 AGN, NGC 2110, and utilize 2–20 keV X-ray variation monitored by MAXI to trace disc emission, instead of optical/UV variation. Comparing it with light curves in the WISE infrared (IR) W 1 band (λ =3.4 μ m) and W 2 band (λ =4.6 μ m) with cross-correlation analyses, we found candidates of the dust reverberation time lag at ∼60, ∼130, and ∼1250 d between the X-ray flux variation and those of the IR bands. By examining the best-fitting X-ray and IR light curves with the derived time lags, we found that the time lag of ∼130 d is most favoured. With this time lag, the relation between the time lag and luminosity of NGC 2110 is consistent with those in type 1 AGNs, suggesting that the dust reverberation in NGC 2110 mainly originates in hot dust in the torus innermost region, the same as in type 1 AGNs. As demonstrated by the present study, X-ray and IR simultaneous monitoring can be a promising tool to perform the dust reverberation mapping on type 2 AGNs.